Gut vagal sensory signaling regulates hippocampus function through multi-order pathways - Andrea N. Suarez (Nature Portfolio, 2018)
Feeding-relevant vagal signaling occurs between the gastrointestinal tract and the brain, but it is unclear if this pathway influences cognitive processes. This study shows that endogenous gastrointestinal derived vagal sensory signaling promotes hippocampal-dependent memory function via a multi-order brainstem–septal pathway.